Calreticulin Fragment 39-272 Promotes B16 Melanoma Malignancy through Myeloid-Derived Suppressor Cells In Vivo - He, Xiao-Yan; Gong, Fang-Yuan; Chen, Yong; Zhou, Zhe; Gong, Zheng; Gao, Xiao-Ming (Frontiers in Immunology, 2017)
Calreticulin (CRT), a multifunctional Ca2+-binding glycoprotein mainly located in the endoplasmic reticulum, is a tumor-associated antigen that has been shown to play protective roles in angiogenesis suppression and anti-tumor immunity. We previously reported that soluble CRT (sCRT) was functionally similar to heat shock proteins or damage-associated molecular patterns in terms of ability to activate myeloid cells and elicit strong inflammatory cytokine productions. In the present study, B16 melanoma cell lines expressing recombinant CRT fragment 39-272 (sCRT/39-272) in secreted form (B16-CRT), or enhanced green fluorescence protein (rEGFP) (B16-EGFP), were constructed for further investigation on the roles of sCRT in tumor development. When s.c. inoculated into C57BL/6 mice, the B16-CRT cells were significantly more aggressive (in terms of solid tumor growth rate) than B16-EGFP controls in a TLR4- and myeloid derived suppressor cells (MDSC)-dependent manner. The B16-CRT-bearing mice showed increased Gr1+ MDSC infiltration in tumor tissues, accelerated proliferation of CD11b+Ly6G+Ly6Clow (G-MDSC) precursors in bone marrow, and higher percentages of G-MDSCs in spleen and blood, which was mirrored by decreased percentage of dendritic cells (DC) in periphery. In in vitro studies, recombinant sCRT/39-272 was able to promote migration and survival of tumor-derived MDSCs via interaction with TLR4, inhibit MDSC differentiation into DC, and also elicit expression of inflammatory proteins S100A8 and S100A9 which are essential for functional maturation and chemotactic migration of MDSCs. Our data provides solid evidence for CRT as a double-edged sword in tumor development.